Legal Regulation of Building Utilization Policy in Parepare City: Between Plan and Reality - Ifa Nurul Ilmah; Indah Fitriani Sukri; La Ode Muhammad Taufiq Afoeli (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
This research examines the utilization of buildings in Parepare City based on Regional Regulation No. 5/2014 on Building and the effectiveness of supervision conducted by the local government. This research uses a qualitative approach with a social/empirical method. Data were obtained through observation, interviews, and documentation. The results showed that building utilization in Parepare City is not always in accordance with the initial designation. Some buildings have changed functions, such as the culinary market building which turned into a public service office to optimize its utilization, Building 202 which was abandoned after a change in function, and the Jiwasraya building which is not operating due to bankruptcy. Supervision by the PUPR Office is structured, but still faces obstacles in changing the function of buildings and the lack of optimal socialization and supervision. In the perspective of Siyasah Idariyah, the Parepare City Government is responsible for maintaining spatial order and protecting the community from the negative impact of building conversion. The principles of shura and accountability are applied in policy making, with the use of technology and persuasive approaches to increase public awareness. This step is in line with the principles of benefit and responsibility in Islam.